Development of schoolpreneur model for Malaysian secondary school: a confirmatory factor analysis approach - Sharul Effendy Janudin (Tanjung Malim, 2023)
Development of schoolpreneur model for Malaysian secondary school: a confirmatory factor analysis approach by Sharul Effendy Janudin